2015
DOI: 10.1111/puar.12430
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Motivation Research: Achievements, Challenges, and Future Directions

Abstract: This article takes stock of public service motivation research to identify achievements, challenges, and an agenda for research to build on progress made since 1990. After enumerating achievements and challenges, the authors take stock of progress on extant proposals to strengthen research. In addition, several new proposals are offered, among them conducting more research on the disaggregated construct, developing grounded theory of public service motivation to understand contextual variations across cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(193 citation statements)
references
References 65 publications
(89 reference statements)
4
170
0
10
Order By: Relevance
“…Studies focusing on work engagement and inherently pride showed that commitment with the organization, job satisfaction, and public service motivation are job attitudes which work in tandem to produce organizational outcomes (Albrecht et al, 2015;Perry & Vandenabeele, 2015). Lavigna (2015) argues that public organizations should recruit and retain employees who have a high degree of PSM and then build on that gene to drive high levels of engagement and inherently pride.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on work engagement and inherently pride showed that commitment with the organization, job satisfaction, and public service motivation are job attitudes which work in tandem to produce organizational outcomes (Albrecht et al, 2015;Perry & Vandenabeele, 2015). Lavigna (2015) argues that public organizations should recruit and retain employees who have a high degree of PSM and then build on that gene to drive high levels of engagement and inherently pride.…”
Section: Theorymentioning
confidence: 99%
“…It is a deep personality trait of individuals who are willing to engage in sacrificial behavior for the good of citizens without reciprocal benefits for themselves (Perry & Vandenabeele, 2015). Many employees enter public service because they are already committed to the mission of government (Lavigna, 2013).…”
Section: Factors From the Jd-r Modelmentioning
confidence: 99%
“…The two most important factors mentioned are the bureaucratic structures and especially the perceived red tape, and the specific motivation of public servants to work in the public sector (PSM; Kernaghan, 2011). Despite the attention to these factors in public administration literature (Loon, van Leisink, Knies, & Brewer, 2016;Perry & Vandenabeele, 2015), they have barely been empirically related to the JD-R model in general (an exception is Giauque, Anderfuhren-Biget, & Varone, 2012), let alone to the JD-R model of work engagement in particular (Bakker, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…psm has been one of the concepts peculiar to the field of public administration (Perry and Vandenabeele 2015), which swung back to public values, which, once again, is seen as the moving force within the public organizations (O'Flynn 2007). psm is characterized as a reliance on intrinsic rewards (e.g.…”
Section: Introductionmentioning
confidence: 99%